Optimization and validation of a real-time PCR method for the simultaneous detection of Lactococcus garvieae and Streptococcus agalactiae in fish - Taona Zinyakasa; Farisai Chidzwondo; Tatenda Makawa; Sitokozile Sibanda; Exnevia Gomo; Tivapasi Musa; Elizabeth Gori (Journal of BioScience and Biotechnology)
Background: Lactococcus garvieae and Streptococcus agalactiae infections contribute to heavy losses in aquaculture farms worldwide. Currently, available pathogen diagnostic tools use biochemical and microbiological methods beleaguered by very low accuracy, reproducibility and specificity. Aim: To optimize and validate a rapid, sensitive and specific real-time PCR (qPCR) method for detecting L. garvieae and S. agalactiae in fish. Methods: Pairs of Streptococcus-specific (IGS-s/IGS-a) and Lactococcus-specific (CAU12F/CAU15R) primers were tested for specificity and sensitivity in the qPCR. qPCR was carried out at different temperatures and primer concentrations. The optimal conditions were determined to be the temperature and primer concentration with the lowest CT values. Results: For both primer sets, the optimal annealing temperature was 60oC, and the optimal primer concentration was 500 nM. The detection limit for L. garvieae was at dilution factor 10-3, with a mean CT value of 25.0, for S. agalactiae, 10-4 with a mean CT value of 29.8. The PCR efficiencies were 97% for L. garvieae and 91% for S. agalactiae, with linear slopes (R2 = 0.999). The assay demonstrated high repeatability and reproducibility. Conclusion: The optimum conditions established for the qPCR method enable rapid, highly sensitive and specific diagnosis of L. garvieae and S. agalactiae infection in fish.